(+)-Z-Bisdehydrodoisynolic Acid Enhances Basal Metabolism and Fatty Acid Oxidation in Female Obese Zucker Rats. (19th April 2012) - Banz, William J.; Strader, April D.; Ajuwon, Kolapo M.; Hou, Yuqing; Meyers, Cal Y.; Davis, Jeremy E.
Abstract : We have previously reported that the synthetic estrogen, (+)- Z -bisdehydrodoisynolic Acid [(+)- Z -BDDA], attenuated weight gain and cardiovascular risk in obese rodents. To determine if these antiobesity effects were attributed to changes in basal metabolism, we assessed indirect calorimetry and metabolic profile in female obese Zucker (OZR) rats provided (+)- Z -BDDA (0.0002% food admixture) for 11 weeks. Similar to our previous findings, (+)- Z -BDDA reduced weight gain and improved lipid and glucose homeostasis in OZR rats. Furthermore, resting energy expenditure was increased by (+)- Z -BDDA, as evident by heat production and oxygen consumption. We also observed a marked reduction in respiratory quotient (RQ) along with a corresponding induction of hepatic AMPK in rodents provided (+)- Z -BDDA. Collectively, these findings indicate that (+)- Z -BDDA partially attenuated obesity and associated pathologies through increased resting energy expenditure and fatty acid utilization. Further investigation is required to fully elucidate the mechanisms involved as well as to determine the potential therapeutic implications for (+)- Z -BDDA on obesity and its related pathologies.